2010
DOI: 10.3109/14756366.2010.515215
|View full text |Cite
|
Sign up to set email alerts
|

A FLT3-inhibitory constituent from the rhizomes of Anemarrhena asphodeloides

Abstract: Bioactivity-guided investigation for the rhizomes of Anemarrhena asphodeloides using the Fms-like tyrosine kinase 3 (FLT3) inhibition assay led to the identification of an active xanthone, mangiferin. Mangiferin was found to inhibit activity of the FLT3 wild type and a mutated form of FLT3 with IC 50 values of 0.7 and 1.2 μM, respectively. Furthermore, this compound was assessed with a small panel of select kinases anaplastic lymphoma kinase (ALK), insulin receptor, and epidermal growth factor receptor) and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Some of the compounds evaluated in this study have been reported in previous studies. 26,27,31,32 Compounds 10,11,12,13,34,35,36,37,38,39, and 40 were synthesized by a total synthesis strategy, as described in previous studies. 26,27 In another prior investigation, a semisynthesis strategy was used to afford compounds 21, 22, 23, 24, and 26 from isolated prenylated flavanones.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the compounds evaluated in this study have been reported in previous studies. 26,27,31,32 Compounds 10,11,12,13,34,35,36,37,38,39, and 40 were synthesized by a total synthesis strategy, as described in previous studies. 26,27 In another prior investigation, a semisynthesis strategy was used to afford compounds 21, 22, 23, 24, and 26 from isolated prenylated flavanones.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Previous studies have shown the potential antitumor properties of flavonoids . Flavonoids are common secondary metabolites and dietary phytochemicals found in plants with potential benefits for cancer therapy. They are currently used widely as components in nutraceutical, cosmetic, and pharmaceutical applications . Flavonoids contain a phenylbenzopyrone (C 6 –C 3 –C 6 ) structural motif. , Classification of flavonoids is based on variations of ring C and contains several major subclasses, including chalcones, flavanones, flavones, flavonols, isoflavones, neoflavones, aurones, and anthocyanins. , The activity of these compounds is attributed to their ability to provide electrons from the phenolic hydroxy groups and the possession of a scaffold susceptible to charge-transfer interactions. , In addition, the potent antioxidant and free-radical scavenging activities of flavonoids appear to have health benefits .…”
mentioning
confidence: 99%